The basics of cloud computing understanding the fundamentals of cloud computing in theory and practice - Rountree, Derrick; Castrillo, Ileana (Basics, 2013)
As part of the Syngress Basics series, The Basics of Cloud Computing provides readers with an overview of the cloud and how to implement cloud computing in their organizations. Cloud computing continues to grow in popularity, and while many people hear the term and use it in conversation, many are confused by it or unaware of what it really means. This book helps readers understand what the cloud is and how to work with it, even if it isn't a part of their day-to-day responsibility